(untitled) (Editora Impacto Científico, 2025)
Objective: To analyze the hospital and economic burden of appendiceal diseases (ICD-10 K35–K37) in the Brazilian Unified Health System (SUS) between 2008 and 2024, according to Brazilian macro-regions. Methods: Descriptive ecological study with data from SIH/DATASUS (TabNet). Hospitalizations, deaths, average length of stay, and hospital costs were evaluated. The mortality rate and average cost per hospitalization were calculated. Results: During the analyzed period, there were 1,911,667 hospitalizations and 7,025 deaths (mortality rate of 0.37%), with a total cost of R 1.25 billion. The Southeast region concentrated 38.8% of hospitalizations; the South region presented the lowest mortality rate (0.25%). Conclusion: Regional heterogeneity was identified in the analyzed indicators, with implications for surgical management and the planning of public health policies. DOI: https://doi.org/10.56238/edimpacto2025.091-021